Popular fermented foods and beverages in Southeast Asia - Law, Se Vern; Abu Bakar, Fatimah; Mat Hashim, Dzulkifly; Abdul Hamid, Azizah (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2011)
Fermented foods are prevalent in Southeast Asia to balance the fluctuation in food availability in the area during the stage of monsoonal circulation. Techniques of preserving cereal and seafood products are well-developed in Southeast Asia. The review concerning the indigenous carbohydrate-based fermented foods the region, including rice wine, fermented palm sap and tapai. The paper focuses on the popular indigenous fermented foods and beverages produced in the region including the consumption and processing methods. Microbiological and chemical properties of these indigenous fermented foods were also discussed. Another issue is in the alcohol-related health risk due to the consumption of the foods and beverages with high alcohol content. Hence, ethanol and other alcohol-related compounds present in the selected alcoholic fermented foods will be highlight.